2017
DOI: 10.1123/ijspp.2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

The Unsuitability of Energy Expenditure Derived From Microtechnology for Assessing Internal Load in Collision-Based Activities

Abstract: This aim of this study was to examine the validity of energy expenditure derived from microtechnology when measured during a repeated-effort rugby protocol. Sixteen male rugby players completed a repeated-effort protocol comprising 3 sets of 6 collisions during which movement activity and energy expenditure (EE) were measured using microtechnology. In addition, energy expenditure was estimated from open-circuit spirometry (EE). While related (r = .63, 90%CI .08-.89), there was a systematic underestimation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 0 publications
2
50
1
Order By: Relevance
“…While a metabolic power approach has been used previously in other sports (Polglaze et al, 2017;Coutts et al, 2015), we acknowledge the possible underestimation of EE during match play by employing this method (Highton et al, 2016;Buchheit et al, 2015). Furthermore, data were gathered from a small sample size from one female International Touch squad during a single tournament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a metabolic power approach has been used previously in other sports (Polglaze et al, 2017;Coutts et al, 2015), we acknowledge the possible underestimation of EE during match play by employing this method (Highton et al, 2016;Buchheit et al, 2015). Furthermore, data were gathered from a small sample size from one female International Touch squad during a single tournament.…”
Section: Discussionmentioning
confidence: 99%
“…7.2 ± 1.0 cf. 13.2 ± 3.2 Kcal•min -1 ; Highton et al, 2016), it possesses a stronger association with EE (r = 0.63) than other measures such as high-speed distance (r = 0.50) or Player Load™ (r = 0.37; Highton et al, 2016). Given this method has been employed with other non-contact team sports (Polglaze et al, 2017), the metabolic power model offers a useful approach to understand the energy demands of Touch.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the agreement between P GPS and P VO2 has only been shown to be acceptable during continuous and linear jog and runs (but neither during walking nor intermittent changes of direction runs), 27 the metabolic underestimation consistently reported [26][27][28][29] may be related to the fact that the current equation initially developed for maximal and linear sprint acceleration 21 may not be well suited for team-sport-specific running patterns (eg, including . The shorter the window, the greater the acceleration value.…”
Section: Adding Value To Load-monitoring Systems?mentioning
confidence: 99%
“…P GPS was actually reported to be very largely greater than P VO2 during walking 27 but very largely lower during shuttle runs at low speed 28 and during soccer-, 26 rugby-, 29 or team-sport-specific 27 circuits. While some may see the consistency of such conclusions as a kind of consensus, Osgnach et al 30 suggested that some methodological errors may explain the underestimation of P GPS reported.…”
Section: What Are We Measuring In the End?mentioning
confidence: 99%
See 1 more Smart Citation